Data Warehousing: Architecture and Implementation - Humphries, Mark; Hawkins, Michael; Dy, Michelle (Harris Kern's Enterprise computing institute., 1998)
8090B-0 A start-to-finish process for deploying successful data warehouses. This book delivers what every data warehousing project participant needs most: a thorough overview of today's best solutions, and a reliable step-by-step process for building warehouses that meet their objectives. It answers the key questions asked by everyone involved in a data warehouse initiative: project sponsors, developers, managers, and CIOs. And, with over 75 figures, it doesn't just tell you how to get the job done: it shows you. Migration strategies and scenarios Management and support: issue resolution, capacity planning, security, backup, and more Specific answers for project sponsors, managers, and CIOs 12 steps for implementation Best techniques for schema design and metadata Choosing the right hardware, software, and platforms Evolving as new technologies mature Rely on this book's up-to-date listings of vendors and Web resources. Learn to evolve your data warehouse as new technologies mature-including metadata interchange standards, Web solutions, and Windows ...Ø NT. Whatever your goals, Data Warehousing for IT Professionals will help you achieve them faster and at lower cost.